Bentuk-bentuk Kekuasaan dalam Pemanfaatan Tanah Ulayat di Kabupaten Kampar - Wan Asrida; Raja Amin; Auradian Marta (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2018)
This research attempts to analyze the forms of power in the utilization of communal land in Kampar Regency. The interests of indigenous peoples in terms of ulayat land tenure feel threatened by the existence of plantation corporations by bringing large investments which ultimately provide economic added value for the Government and Regional Government. This study uses qualitative research methods with a phenomenological approach. Data was obtained through interviews conducted with elements of the Kampar District Government, Lembaga Adat Kampar (LAK), the Archipelago Indigenous Peoples Alliance (AMAN) Kampar, and traditional leaders. Technical data analysis in this study was conducted interactively. The argument from this study shows that there are 2 (two) forms of power that influence the implementation of ulayat land use in Kampar Regency. The first is visible power, where the practice of power occurs in the formal sphere in the policy-making process of recognizing and protecting customary law communities in Kampar District. In addition, the practice of visible power is also evident from the interaction between actors in resolving communal land conflicts that occurred in Kampar District. While the second form of power in the utilization of communal land is hidden power. This hidden power practice is carried out by corporate actors who are suspected of taking over customary land by playing their power in licenses issued by the Government.